1996
DOI: 10.1002/(sici)1522-7154(1996)2:3<109::aid-anxi1>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Short-term rebound anxiolytic effects and long-term changes in platelet benzodiazepine binding after pentylenetetrazole-kindling in two strains of rat

Abstract: Although there were no differences in response to an acute injection of pentylenetetrazole (PTZ), there were strain differences in the development of kindled seizures to repeated injections (PTZ; 30 mg/kg 3 times weekly for 13 injections), with Wistar rats reaching stage 4 or 5 of clonic‐tonic seizures, but hooded Lister rats reaching only stage 2 or 3 of convulsive waves axially through the body. The strains also reacted differently to a test dose of PTZ (20 mg/kg) one week after the end of kindling, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Anxiety in rats may inhibit exploratory behavior [39]. The administration of pentylenetetrazole is reported by some studies to produce an anxiolytic effect [40,41], while other studies reported higher anxiety levels [30,42]. A limitation of this study is that anxiety was not assessed independently.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety in rats may inhibit exploratory behavior [39]. The administration of pentylenetetrazole is reported by some studies to produce an anxiolytic effect [40,41], while other studies reported higher anxiety levels [30,42]. A limitation of this study is that anxiety was not assessed independently.…”
Section: Discussionmentioning
confidence: 99%